Ecofriendly Fabrication and Hierarchical Exploration of Cytocompatible Lignin Nanoparticles for Biomedical Applications. - Mohanty, P.K.; Kumari, N.; Kerry, R.G.; Ray, A.; Bhol, N.K.; Panigrahi, B.; Majhi, S.; Rath, P.K.; Nayak, S.; Badamali, S.K. (ACS applied bio materials, 2025)
Lignin, the most abundant renewable aromatic biopolymer, offers significant potential for bionanomaterial innovation in biomedical applications. This study presents a facile method for isolating soda lignin from waste coconut shells, followed by its standard characterizations and the design of lignin nanoparticles (LNPs) using a greener approach. A hierarchical exploration of the LNPs was performed, encompassing structural and molecular characterizations, in vitro enzymatic as well as cellular studies, in vivo assays using Drosophila melanogaster (D. melanogaster) as a model organism, in silico molecular docking, and molecular dynamics simulations. The resulting LNPs exhibited well-defined nanostructures with an average hydrodynamic diameter (DH) of 86.59 ± 2.6 nm (DLS measurement), a spherical morphology (?55 nm from FESEM measurement), hollow nanoarchitecture (pore diameter ?60 nm), high colloidal stability (zeta potential: -41.1 ± 1.1 mV), and a broad emission spectrum (270-600 nm). Additionally, advanced techniques such as micro-FTIR, micro-Raman, XRD (X-ray diffraction), and TGA-DSC studies further validated the successful LNP synthesis and structural integrity. In vitro and in vivo bioactivity studies with D. melanogaster demonstrated that LNPs significantly outperform bulk lignins in terms of antidiabetic, antioxidant, and cytotoxicity properties. In silico molecular docking and molecular dynamics simulation studies supported these findings. The in vitro antidiabetic assay showed inhibition activities of 53.27 ± 1.3% (?-amylase) and 66.23 ± 1.5% (?-glucosidase) at 10 ?g/mL, similar to the standard inhibitor acarbose. The LNPs exhibited strong antioxidant activity (56.6 ± 0.6% at 10 ?g/mL), comparable to allopurinol (77.33 ± 1.4%). Along with this, LNPs displayed enhanced catalase activity (1.2-fold), reduced ROS levels (0.3-fold at 1 ?g/mL), maintained glutathione levels, and did not increase H2O2 levels that might induce oxidative stress. MTT assays confirmed good biocompatibility in HCT cells, while in vivo acute toxicity studies with D. melanogaster indicated higher survivorship than bulk lignins.